A nanofiltration membrane and its preparation method

Through the interfacial polymerization method, the active layer was formed on the nanofiltration membrane, and the p-CCG-COF-TpPa/TpBD and other components were used to solve the problem of insufficient flux and selectivity of the existing nanofiltration membrane, and the efficient removal of heavy metal ions was achieved. and improve sewage treatment efficiency.

CN118807467BActive Publication Date: 2025-01-17HUNAN KEENSEN TECH CO LTD

Patent Information

Application Number
CN202411308166.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-17
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The existing nanofiltration membranes have low retention rates in removing heavy metal ions and insufficient flux, which affects the efficiency of wastewater treatment.

Method used

The nanofiltration membrane was prepared by interfacial polymerization. By forming an active layer on the base membrane, p-CCG-COF-TpPa/TpBD was used as the aqueous solution component, combining sodium hydroxide and surfactant to form a highly selective and high-throughput nanofiltration membranes.

Benefits of technology

The separation performance and flux of the nanofiltration membrane are improved, the high selectivity for heavy metal ions is enhanced, the antibacterial properties are enhanced, the morphology and charge characteristics of the membrane are optimized, and the removal rate of heavy metal ions is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118807467B_ABST
    Figure CN118807467B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of water treatment technology, and in particular to a nanofiltration membrane and a preparation method thereof. The nanofiltration membrane comprises: a base membrane; and an active layer formed on the upper surface of the base membrane; the active layer is formed by an aqueous phase solution and an oil phase solution through an interfacial polymerization reaction and then subjected to heat treatment; the solute of the aqueous phase solution is composed of raw material components including aqueous phase monomers, surfactants, sodium hydroxide and p-CCG-COF-TpPa / TpBD; the p-CCG-COF-TpPa / TpBD is prepared by ultrasonication and suction filtration of a p-CCG dispersion and a COF solution; the p-CCG is obtained by modifying graphene oxide nanosheets with a 1-(3-aminopropyl)-3-methylimidazole brominating agent. The nanofiltration membrane provided by the present invention has excellent separation performance and high flux, and has high selectivity for heavy metal ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water treatment, and in particular to a nanofiltration membrane and a preparation method thereof. Background Art

[0002] Traditional methods such as precipitation, ion exchange, adsorption and solvent extraction can remove heavy metal ions to a certain extent, but there are still some inevitable disadvantages. Compared with the above traditional technologies, membrane separation technology has the advantages of simple operation, low energy consumption, small space requirements, and deep purification, and is more suitable for the removal of heavy metal ions. Reverse osmosis and nanofiltration are two membrane systems that are often used to concentrate and remove metal ions. Reverse osmosis has the characteristics of low permeability flux, poor selectivity for monovalent / polyvalent ions, high working pressure, and high energy requirements, while nanofiltration has higher permeability, better monovalent / polyvalent ion selectivity and lower working pressure, so nanofiltration is a better choice for concentrating and removing heavy metal ions.

[0003] Existing nanofiltration membranes are usually prepared by phase conversion and interfacial polymerization. The nanofiltration membrane prepared by phase conversion has the disadvantage of low flux, so the nanofiltration membrane prepared by interfacial polymerization has a broader application prospect in the field of water treatment.

[0004] The current mainstream commercial rolled nanofiltration membrane is prepared by interfacial polymerization of piperazine and trimesoyl chloride. Its surface carries a negative charge, which is not conducive to the removal of heavy metal ions by the Donnan effect. In addition, due to electrostatic attraction, the adsorption of heavy metal ions on the negatively charged membrane surface is aggravated, thereby reducing the anti-fouling performance of the membrane and the membrane pores are easily blocked. High positively charged nanofiltration membrane technology is recognized as one of the effective methods for effectively removing polyvalent heavy metal ions. However, their charge characteristics often have disadvantages, such as low permeability and poor anti-fouling performance. Therefore, these positively charged membranes must be further modified.

[0005] Furthermore, the improvement of the solvent permeability of the membrane is accompanied by poor compatibility between the additive and the polyamide PA layer. This non-selective interface gap degradation often leads to a decrease in the separation performance of the membrane. How to enhance the compatibility of the polyamide layer with the additive, solve the problem of its low flux, and further improve the flux and separation performance of the nanofiltration membrane is a problem that needs to be solved in this technical field.

[0006] Therefore, the existing nanofiltration membranes and preparation processes have a low retention rate for heavy metal ions such as Cr, Ni and Cu, which makes the current nanofiltration membranes inefficient in treating wastewater. There is an urgent need to develop a nanofiltration membrane with a high heavy metal retention rate and high flux. Summary of the invention

[0007] In view of this, the technical problem to be solved by the present invention is to provide a nanofiltration membrane and a preparation method thereof. The nanofiltration membrane provided by the present invention has excellent separation performance and high flux, and has high selectivity for heavy metal ions.

[0008] The present invention provides a nanofiltration membrane, comprising:

[0009] Basement membrane;

[0010] and an active layer formed on the upper surface of the base film;

[0011] The active layer is formed by interfacial polymerization of an aqueous solution and an oily solution and then heat treatment;

[0012] The solute of the aqueous phase solution is composed of raw material components including aqueous phase monomers, surfactants, sodium hydroxide and p-CCG-COF-TpPa / TpBD;

[0013] The p-CCG-COF-TpPa / TpBD is prepared by ultrasonication and filtration of p-CCG dispersion and COF solution;

[0014] The p-CCG is obtained by modifying graphene oxide nanosheets with 1-(3-aminopropyl)-3-methylimidazole brominating agent.

[0015] Preferably, in the aqueous solution, the mass content of p-CCG-COF-TpPa / TpBD is 0.05%~5%.

[0016] Preferably, the COF is at least one of TpPa-1, TpPa-2, TpPa-NH2, TpPa-F4, TpBD, TpBD-Me2 and TpBD-(OMe)2.

[0017] Preferably, the preparation method of p-CCG comprises the following steps:

[0018] After mixing the aqueous dispersion of graphene oxide nanosheets and 1-(3-aminopropyl)-3-methylimidazole brominating agent, the pH value of the mixed solution is adjusted to 7.5-8.5, and after ultrasonic treatment, heated and stirred, and centrifuged, p-CCG is obtained.

[0019] Preferably, the preparation method of p-CCG-COF-TpPa / TpBD comprises the following steps:

[0020] After mixing the p-CCG dispersion with the COF solution, ultrasonic treatment and vacuum filtration were performed to obtain p-CCG-COF-TpPa / TpBD;

[0021] In the aqueous solution, the mass content of p-CCG-COF-TpPa / TpBD is 0.05%~5%.

[0022] Preferably, the aqueous phase monomer includes at least one of m-phenylenediamine, p-phenylenediamine, piperazine, polyethyleneimine, 3,5-diamino-N-(4-aminophenyl)benzamide and imine COFs;

[0023] In the aqueous phase solution, the mass content of the aqueous phase monomer is 1% to 3%.

[0024] Preferably, the surfactant includes at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and sodium fatty alcohol ether sulfate;

[0025] In the aqueous phase solution, the mass content of the surfactant is 0.01% to 1%.

[0026] Preferably, in the aqueous solution, the mass content of sodium hydroxide is 0.2% to 3.5%.

[0027] Preferably, the oil phase solution consists of acyl chloride and an organic solvent;

[0028] The acyl chloride comprises at least one of phthaloyl chloride, isophthaloyl chloride, terephthaloyl chloride, trimesoyl chloride and pyromellitoyl chloride;

[0029] In the oil phase solution, the mass concentration of acyl chloride is 0.1% to 0.3%;

[0030] The organic solvent includes at least one of trichlorotrifluoroethane, n-hexane, cyclohexane, isopar G, isopar M, isopar L and heptane.

[0031] The present invention also provides a method for preparing the nanofiltration membrane described above, comprising the following steps:

[0032] The base membrane is immersed in an aqueous solution, taken out and dried, immersed in an oil solution for polymerization, taken out, and subjected to heat treatment to obtain a nanofiltration membrane;

[0033] The solute of the aqueous phase solution is composed of raw material components including aqueous phase monomers, surfactants, sodium hydroxide and p-CCG-COF-TpPa / TpBD;

[0034] The p-CCG-COF-TpPa / TpBD is prepared by ultrasonication and filtration of p-CCG dispersion and COF solution;

[0035] The p-CCG is obtained by modifying graphene oxide nanosheets with 1-(3-aminopropyl)-3-methylimidazole brominating agent.

[0036] The present invention provides a nanofiltration membrane, comprising: a base membrane; and an active layer formed on the upper surface of the base membrane; the active layer is formed by an aqueous solution and an oil phase solution through interfacial polymerization and then subjected to heat treatment; the solute of the aqueous solution is composed of raw material components including aqueous monomers, surfactants, sodium hydroxide and p-CCG-COF-TpPa / TpBD; the p-CCG-COF-TpPa / TpBD is prepared by ultrasonic and suction filtration of a p-CCG dispersion and a COF solution; the p-CCG is obtained by modifying graphene oxide nanosheets with a 1-(3-aminopropyl)-3-methylimidazole brominating agent. The present invention overcomes the shortcomings of the prior art and provides a nanofiltration membrane with high selectivity for heavy metal ions by introducing p-CCG-COF-TpPa / TpBD into an aqueous phase of metaphenylenediamine (MPD) during interfacial polymerization. In this method, p-CCG provides a channel for directional diffusion, and the electrostatic interaction with the polyamide chain enhances the overall compatibility and long-term stability of the composite membrane, while COF-TpPa / TpBD effectively provides an additional solvent transmission channel for the nanofiltration membrane. The membrane morphology is regulated by the electrostatic attraction between p-CCG-COF-TpPa / TpBD and the aqueous phase reaction monomer in the aqueous phase. The experimental results show that the nanofiltration membrane provided by the present invention has better separation performance and higher flux, specifically, better removal rate for MgCl2·6H2O; high selectivity for heavy metal ions, and better antibacterial performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The composite nanofiltration membranes of Examples 1, 4 and Comparative Example 1 were used to measure Cu 2+ Removal rate of

[0038] Figure 2 The composite nanofiltration membranes of Examples 1, 4 and Comparative Example 1 are Ni 2+ Removal rate of

[0039] Figure 3 The composite nanofiltration membranes of Examples 1, 4 and Comparative Example 1 were used to measure the Cr 2+ Removal rate of

[0040] Figure 4 The composite nanofiltration membranes of Examples 1, 4 and Comparative Example 1 were 2+ Removal rate of

[0041] Figure 5 The antibacterial effect of the composite nanofiltration membranes of Examples 1, 3, 5, 7 and Comparative Example 1 on Escherichia coli;

[0042] Figure 6 The antibacterial effect of the composite nanofiltration membranes of Examples 1, 3, 5, 7 and Comparative Example 1 on Staphylococcus aureus;

[0043] Figure 7 The infrared spectra of PA, COF-TpPa, p-CCG and p-CCG-COF-TpPa-PA;

[0044] Figure 8 The membrane surface charge properties of the composite nanofiltration membranes of Examples 2, 4, 6 and Comparative Example 1. DETAILED DESCRIPTION

[0045] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] The present invention provides a nanofiltration membrane, comprising:

[0047] Basement membrane;

[0048] and an active layer formed on the upper surface of the base film;

[0049] The active layer is formed by interfacial polymerization of an aqueous solution and an oily solution and then heat treatment;

[0050] The solute of the aqueous phase solution consists of an aqueous phase monomer, a surfactant, sodium hydroxide and p-CCG-COF-TpPa / TpBD;

[0051] The p-CCG-COF-TpPa / TpBD is prepared by ultrasonication and filtration of p-CCG dispersion and COF solution;

[0052] The p-CCG is obtained by modifying graphene oxide nanosheets (GO) with 1-(3-aminopropyl)-3-methylimidazolium bromination agent (IL-NH2).

[0053] In certain embodiments of the present invention, the material of the base membrane is at least one of polyphenylsulfone (PPSU), polyaniline (PANI), polysulfone (PSF), polyetheretherketone (PEEK), polyimide (PI), polybenzimidazole (PBI), polyvinylidene fluoride (PVDF) and polyethersulfone; the molecular weight cutoff of the base membrane is 50~200 KDa.

[0054] In the aqueous solution:

[0055] In the present invention, the solute of the aqueous phase solution consists of aqueous phase monomers, surfactants, sodium hydroxide and p-CCG-COF-TpPa / TpBD.

[0056] The aqueous phase monomer is a polyamine monomer, specifically at least one of m-phenylenediamine (MPD), p-phenylenediamine, piperazine (PIP), polyethyleneimine (PEI), 3,5-diamino-N-(4-aminophenyl)benzamide and I-CoFs (imine COFs). The I-COFs are TpPa (such as at least one of TpPa-1, TpPa-2, TpPa-NH2 and TpPa-F4) or TpBD (such as at least one of TpBD, TpBD-Me2 and TpBD-(OMe)2). The present invention has no special restrictions on the source of the I-COFs, and can be synthesized by referring to the method described in the literature Chandra, et al. Chemically Stable Multilayered Covalent OrganicNanosheets from Covalent Organic Frameworks via Mechanical Delamination. J AmChem Soc, 2013, 135(47): 17853).

[0057] In certain embodiments of the present invention, the mass content of the aqueous phase monomer in the aqueous phase solution is 1% to 3%, for example, 1.2%.

[0058] In certain embodiments of the present invention, the surfactant is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and sodium fatty alcohol ether sulfate. In the aqueous phase solution, the mass content of the surfactant is 0.01% to 1%, such as 0.05%.

[0059] In certain embodiments of the present invention, the mass content of sodium hydroxide in the aqueous solution is 0.2% to 3.5%, for example 0.5%.

[0060] In certain embodiments of the present invention, in the aqueous solution, the mass content of p-CCG-COF-TpPa / TpBD is 0.05% to 5%, for example 0.15%.

[0061] In the present invention, the p-CCG-COF-TpPa / TpBD is prepared by ultrasonication and filtration of p-CCG dispersion and COF solution;

[0062] The p-CCG is obtained by modifying graphene oxide nanosheets (GO) with 1-(3-aminopropyl)-3-methylimidazolium bromide (IL-NH2). Specifically, the p-CCG is obtained by complexing 1-(3-aminopropyl)-3-methylimidazolium bromide (IL-NH2) with graphene oxide nanosheets (GO).

[0063] In certain embodiments of the present invention, the method for preparing p-CCG comprises the following steps:

[0064] After mixing the aqueous dispersion of graphene oxide (GO) nanosheets and 1-(3-aminopropyl)-3-methylimidazolium bromination agent (IL-NH2), the pH value of the mixed solution was adjusted to 7.5-8.5, and after ultrasonic treatment, heated and stirred, and centrifuged, p-CCG was obtained.

[0065] The mass ratio of the graphene oxide nanosheets to IL-NH2 is 3-7:8-12, such as 5:10.

[0066] The concentration of the aqueous dispersion of graphene oxide (GO) nanosheets is 0.3-0.7 mg / mL, such as 0.5 mg / mL.

[0067] The reagent for adjusting the pH value of the mixed solution is potassium hydroxide, and the pH value of the mixed solution is adjusted to 7.0.

[0068] The power of the ultrasonic treatment is 500-1300 W, such as 500 W, and the time is 25-35 min, such as 30 min. After the ultrasonic treatment, the turbid mixture is converted into a uniform transparent solution.

[0069] The heating and stirring temperature is 75-85°C, such as 80°C; the time is 22-26 hours, such as 24 hours; the speed is 10000-14000 r / min, such as 12000 r / min. The heating and stirring process is the complexing reaction process.

[0070] After the centrifugation, the method further comprises: washing with ethanol and water in sequence, and air drying.

[0071] The present invention has no particular limitation on the source of the graphene oxide (GO) nanosheets. In certain embodiments of the present invention, the method for preparing the graphene oxide (GO) nanosheets comprises the following steps:

[0072] a) suspending graphene oxide in ultrapure water, removing residual salt and acid by dialysis, and obtaining graphene oxide powder by centrifugation and air drying;

[0073] b) dispersing the graphene oxide powder in water, subjecting the powder to ultrasonic treatment, and then exfoliating the powder to obtain graphene oxide nanosheets.

[0074] In step a):

[0075] The present invention has no particular limitation on the source of the graphene oxide, and a method for preparing graphene oxide well known to those skilled in the art, such as the Hummers method, can be used.

[0076] The graphene oxide was suspended in ultrapure water to obtain a brown dispersion. The dialysis time was 4 days.

[0077] In step b):

[0078] The graphene oxide powder is dispersed in water to obtain a dispersion liquid having a mass concentration of 0.05%.

[0079] The power of the ultrasonic treatment is 500-1300 W, such as 1300 W; the time is 0.8-1.2 h, such as 1 h.

[0080] The present invention has no particular restrictions on the source of the 1-(3-aminopropyl)-3-methylimidazole brominating agent (IL-NH2). In certain embodiments of the present invention, the preparation method of the 1-(3-aminopropyl)-3-methylimidazole brominating agent (IL-NH2) comprises the following steps:

[0081] 3,5-Bromopropylamine hydrobromide, 1-methylimidazole and ethanol were mixed and refluxed under nitrogen. The resulting turbid mixture was purified by crystallization to obtain 1-(3-aminopropyl)-3-methylimidazole brominating agent (IL-NH2).

[0082] The molar ratio of the 3,5-bromopropylamine hydrobromide to 1-methylimidazole is 1:1.

[0083] The ratio of the sum of the molar amounts of the 3,5-bromopropylamine hydrobromide and 1-methylimidazole to the ethanol is 10 mmol:12.5 mL.

[0084] The reflux temperature is 75-85° C., such as 80° C., and the reflux time is 22-26 h, such as 24 h.

[0085] The crystallization purification uses ethanol. After the crystallization purification, the method further includes: re-purification by an anti-solvent method, wherein the anti-solvent used in the anti-solvent method is ethyl acetate.

[0086] In certain embodiments of the present invention, the preparation method of p-CCG-COF-TpPa / TpBD comprises the following steps:

[0087] The p-CCG dispersion was mixed with the COF solution, subjected to ultrasonic treatment, and vacuum filtered to obtain p-CCG-COF-TpPa / TpBD.

[0088] The p-CCG dispersion is an aqueous dispersion of p-CCG; specifically, it is obtained by dispersing p-CCG in distilled water and ultrasonically treating it; the concentration of the p-CCG dispersion is 8-12 mg / L, such as 10 mg / L; the power of the ultrasonic treatment is 500-900 W, such as 500 W; and the time is 0.8-1.2 h, such as 1 h.

[0089] The COF solution is a DMF (N,N-dimethylformamide) solution of COF; specifically, the COF solution is obtained by dissolving COF powder in DMF and ultrasonically treating the solution; the concentration of the COF solution is 0.03-0.07 mg / mL, such as 0.05 mg / mL; the power of the ultrasonic treatment is 800-1000 W, such as 1000 W; and the time is 1-3 h, such as 2 h.

[0090] The COF powder is TpPa powder (such as at least one of TpPa-1 powder, TpPa-2 powder, TpPa-NH2 powder and TpPa-F4 powder) or TpBD powder (such as at least one of TpBD powder, TpBD-Me2 powder and TpBD-(OMe)2 powder). The present invention has no special restrictions on the source of the COF powder, and reference can be made to

[0091] Chandra, et al. Chemically Stable Multilayered Covalent Organic Nanosheets from Covalent Organic Frameworks via Mechanical Delamination. J Am Chem Soc, 2013, 135(47): 17853).

[0092] After the p-CCG dispersion is mixed with the COF solution, the power of the ultrasonic treatment is 500-1300 W, such as 1300 W, and the time is 3-7 min, such as 5 min.

[0093] In certain embodiments of the present invention, the solvent of the aqueous solution is water, such as RO water (reverse osmosis water).

[0094] The present invention has no particular limitation on the method for preparing the aqueous solution. In certain embodiments of the present invention, the method for preparing the aqueous solution comprises:

[0095] The aqueous phase monomer, surfactant, sodium hydroxide, p-CCG-COF-TpPa / TpBD and water are mixed to obtain an aqueous phase solution.

[0096] In the oil phase solution:

[0097] In the present invention, the oil phase solution consists of acyl chloride and an organic solvent.

[0098] In certain embodiments of the present invention, the acyl chloride is at least one of phthaloyl chloride, isophthaloyl chloride, terephthaloyl chloride, trimesoyl chloride and pyromellitoyl chloride; specifically at least one of 1,3,5-benzene trimecarboxylic acid chloride (TMC), isophthaloyl chloride, 5-isocyanato-isophthaloyl chloride, m-biphenyl tetracarboxylic acid chloride and 5-chloroformyloxy-isophthaloyl chloride. In the oil phase solution, the mass concentration of the acyl chloride is 0.1% to 0.3%.

[0099] The organic solvent is at least one of trichlorotrifluoroethane, n-hexane, cyclohexane, isopar G, isopar M, isopar L and heptane.

[0100] The present invention has no particular limitation on the method for preparing the oil phase solution. In certain embodiments of the present invention, the method for preparing the oil phase solution comprises:

[0101] The acid chloride is dissolved in an organic solvent to obtain an oil phase solution.

[0102] In some embodiments of the present invention, the thickness of the active layer is 25-89 nm, such as 25-60 nm, specifically 30 nm. The thickness of the base film is 145-155 μm, such as 150 μm.

[0103] The present invention also provides a method for preparing the nanofiltration membrane described above, comprising the following steps:

[0104] The base membrane is immersed in an aqueous solution, taken out and dried, immersed in an oil solution for polymerization, taken out, and subjected to heat treatment to obtain a nanofiltration membrane;

[0105] The solute of the aqueous phase solution consists of an aqueous phase monomer, a surfactant, sodium hydroxide and p-CCG-COF-TpPa / TpBD;

[0106] The p-CCG-COF-TpPa / TpBD is prepared by ultrasonication and filtration of p-CCG dispersion and COF solution;

[0107] The p-CCG is obtained by modifying graphene oxide nanosheets with 1-(3-aminopropyl)-3-methylimidazole brominating agent.

[0108] The aqueous phase solution and the oil phase solution are the same as above and will not be described in detail here.

[0109] In certain embodiments of the present invention, the surface drying method comprises:

[0110] Use a roller to roll the surface of the base film to squeeze out the excess liquid and blow dry.

[0111] The polymerization reaction temperature is 30-70° C., such as 45° C., and the polymerization time is 5-120 s, such as 20 s.

[0112] In some embodiments of the present invention, the heat treatment further includes: natural drying in air. The natural drying time in air can be 1 min.

[0113] In some embodiments of the present invention, the heat treatment is performed at a temperature of 35-45° C., such as 40° C., for a time of 5 s-1 min, such as 10 s, 45 s. The heat treatment is performed in an oven.

[0114] In some embodiments of the present invention, after the heat treatment, the process further comprises: rinsing and drying. The rinsing is performed with clean water.

[0115] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.

[0116] The present invention uses 1-(3-aminopropyl)-3-methylimidazolium bromide (IL-NH2) to modify graphene oxide, and the amino group is used as a moisturizer to alleviate the decrease in membrane permeability after appropriate heating treatment; and the imidazole group has high charge. In addition, p-CCG has the function of enhancing solubility and interlayer electrostatic repulsion, and enhancing dispersibility in solution; the edges of graphene oxide nanosheets have carboxyl groups, carboxyl groups, etc., which are also electrostatically attracted by the amide groups on the polyamide chain generated by interfacial polymerization, thereby improving the compatibility of the modified graphene oxide nanosheets and polyamide membranes. p-CCG-COF-TpPa / TpBD is used as an additive in an amine-water solution, and its adjustable functional groups and specific ion diffusion behavior in an aqueous solution are used to regulate the IP process. p-CCG diffuses to the interface between the two phases first, the cationic amine group enters the organic phase and reacts with the organic phase monomer, and the cationic hydrophilic imidazole ring structure remains in the aqueous phase, and p-CCG forms a directional channel at the water-organic interface, which is conducive to the directional diffusion of amine monomers. COF provides additional solvent transfer channels and changes the peak-valley morphology of the membrane surface, increasing the contact area between the membrane and the solvent.

[0117] In order to further illustrate the present invention, a nanofiltration membrane and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments, but it should not be construed as limiting the scope of protection of the present invention.

[0118] The reagents used in the following examples and comparative examples are all commercially available.

[0119] In the embodiment:

[0120] S1) Preparation of graphene oxide (GO) nanosheets:

[0121] S1-1) Graphene oxide prepared by the Hummers method was suspended in ultrapure water to obtain a brown dispersion, which was dialyzed for 4 days to remove residual salt and acid, and then centrifuged and air-dried to obtain graphene oxide powder;

[0122] S1-2) The graphene oxide powder is dispersed in water to obtain a dispersion with a mass concentration of 0.05%, and after ultrasonic treatment (power of 1300 W) for 1 h, it is peeled off to obtain graphene oxide nanosheets.

[0123] S2) Preparation of 1-(3-aminopropyl)-3-methylimidazolium brominating agent (IL-NH2):

[0124] 3,5-Bromopropylamine hydrobromide (1.1000 g, 5 mmol) and 1-methylimidazole (0.395 mL, 5 mmol) were added to 12.5 mL of ethanol to form a colorless solution, which was refluxed at 80 °C under nitrogen for 24 h. The resulting turbid mixture was purified by recrystallization from ethanol and purified again by the antisolvent method with ethyl acetate as the antisolvent to obtain IL-NH2.

[0125] S3) Preparation of p-CCG:

[0126] IL-NH2 (10 mg) was added to 10 mL of 0.5 mg / mL aqueous dispersion of graphene oxide (GO) nanosheets, and then KOH (10 mg) was added to adjust the pH value of the mixed solution to 7.0. After ultrasonic treatment (ultrasonic treatment power was 500 W) for 30 min, the turbid mixture was converted into a uniform transparent solution. It was vigorously stirred at 80°C (speed was 12000 r / min) for 24 h, centrifuged, washed with ethanol and water in sequence, and air-dried to obtain p-CCG.

[0127] S4) Preparation of p-CCG-COF-TpPa / TpBD:

[0128] S4-1) Preparation of p-CCG dispersion: 10 mg p-CCG was dispersed in 1000 mL distilled water and ultrasonically treated (ultrasonication power was 500 W) for 1 h to obtain a 10 mg / L p-CCG dispersion;

[0129] S4-2) Preparation of COF solution: 10 mg COF powder was dissolved in 200 mL DMF and ultrasonicated (ultrasonication power was 1000 W) for 2 h to obtain a 50 mg / L COF solution;

[0130] S4-3) After mixing the p-CCG dispersion and the COF solution, ultrasonic treatment (ultrasonic treatment power is 1300 W) for 5 min, and then vacuum filtration to obtain p-CCG-COF-TpPa / TpBD.

[0131] Example 1

[0132] 1) preparing p-CCG-COF-TpPa-NH2 according to step S4); wherein the COF powder is TpPa-NH2 powder;

[0133] 2) Preparation of aqueous solution:

[0134] Mix m-phenylenediamine, sodium dodecyl sulfate, sodium hydroxide, p-CCG-COF-TpPa-NH2 and water to obtain an aqueous solution; in the aqueous solution, the mass content of m-phenylenediamine is 1.2%, the mass content of sodium dodecyl sulfate is 0.05%, the mass content of sodium hydroxide is 0.5%, and the mass content of p-CCG-COF-TpPa-NH2 is 0.15%;

[0135] 3) Preparation of oil phase solution:

[0136] Dissolve trimesoyl chloride in n-hexane to obtain an oil phase solution with a mass concentration of 0.2%;

[0137] 4) Immerse the polyethersulfone membrane (base membrane, 150 μm) in the aqueous solution for 1 minute, take it out, roll the surface of the base membrane with a roller to squeeze it dry, and blow dry the excess liquid; then immerse it in the oil solution at 45°C for polymerization reaction for 20 seconds, take it out; dry it naturally in the air for 1 minute, and then heat treat it in an oven at 40°C for 45 seconds; rinse it with clean water, and dry it to obtain a composite nanofiltration membrane.

[0138] The composite nanofiltration membrane comprises: a base membrane; and an active layer formed on the upper surface of the base membrane. The thickness of the active layer is 30 nm.

[0139] Example 2

[0140] 1) preparing p-CCG-COF-TpPa-NH2 according to step S4); wherein the COF powder is TpPa-NH2 powder;

[0141] 2) Preparation of aqueous solution:

[0142] Mix m-phenylenediamine, sodium dodecyl sulfate, sodium hydroxide, p-CCG-COF-TpPa-NH2 and water to obtain an aqueous phase solution; in the aqueous phase solution, the mass content of m-phenylenediamine is 1.5%, the mass content of sodium dodecyl sulfate is 0.03%, the mass content of sodium hydroxide is 0.4%, and the mass content of p-CCG-COF-TpPa-NH2 is 0.1%;

[0143] 3) Preparation of oil phase solution:

[0144] Dissolve trimesoyl chloride in n-hexane to obtain an oil phase solution with a mass concentration of 0.2%;

[0145] 4) Immerse the polyethersulfone membrane (base membrane, 150 μm) in the aqueous solution for 1 minute, take it out, roll the surface of the base membrane with a roller to squeeze it dry, and blow dry the excess liquid; then immerse it in the oil solution at 45°C for polymerization reaction for 20 seconds, take it out; dry it naturally in the air for 1 minute, and then heat treat it in an oven at 40°C for 45 seconds; rinse it with clean water, and dry it to obtain a composite nanofiltration membrane.

[0146] The composite nanofiltration membrane comprises: a base membrane; and an active layer formed on the upper surface of the base membrane; the thickness of the active layer is 30 nm.

[0147] Example 3

[0148] 1) preparing p-CCG-COF-TpPa-NH2 according to step S4); wherein the COF powder is TpPa-NH2 powder;

[0149] 2) Preparation of aqueous solution:

[0150] Mix m-phenylenediamine, sodium dodecyl sulfate, sodium hydroxide, p-CCG-COF-TpPa-NH2 and water to obtain an aqueous solution; in the aqueous solution, the mass content of m-phenylenediamine is 1.2%, the mass content of sodium dodecyl sulfate is 0.05%, the mass content of sodium hydroxide is 0.5%, and the mass content of p-CCG-COF-TpPa-NH2 is 0.5%;

[0151] 3) Preparation of oil phase solution:

[0152] Dissolve trimesoyl chloride in n-hexane to obtain an oil phase solution with a mass concentration of 0.2%;

[0153] 4) Immerse the polyethersulfone membrane (base membrane, 150 μm) in the aqueous solution for 1 minute, take it out, roll the surface of the base membrane with a roller to squeeze it dry, and blow dry the excess liquid; then immerse it in the oil solution at 45°C for polymerization reaction for 20 seconds, take it out; dry it naturally in the air for 1 minute, and then heat treat it in an oven at 40°C for 45 seconds; rinse it with clean water, and dry it to obtain a composite nanofiltration membrane.

[0154] The composite nanofiltration membrane comprises: a base membrane and an active layer formed on the upper surface of the base membrane; the thickness of the active layer is 30 nm.

[0155] Example 4

[0156] 1) preparing p-CCG-COF-TpPa-1 according to step S4); wherein the COF powder is TpPa-1 powder;

[0157] 2) Preparation of aqueous solution:

[0158] Mixing m-phenylenediamine, sodium dodecyl sulfate, sodium hydroxide, p-CCG-COF-TpPa-1 and water to obtain an aqueous phase solution; in the aqueous phase solution, the mass content of m-phenylenediamine is 1.2%, the mass content of sodium dodecyl sulfate is 0.05%, the mass content of sodium hydroxide is 0.5%, and the mass content of p-CCG-COF-TpPa-1 is 0.5%;

[0159] 3) Preparation of oil phase solution:

[0160] Dissolve terephthaloyl chloride in n-hexane to obtain an oil phase solution with a mass concentration of 0.2%;

[0161] 4) Immerse the polyethersulfone membrane (base membrane, 150 μm) in the aqueous solution for 1 minute, take it out, roll the surface of the base membrane with a roller to squeeze it dry, and blow dry the excess liquid; then immerse it in the oil solution at 45°C for polymerization reaction for 20 seconds, take it out; dry it naturally in the air for 1 minute, and then heat treat it in an oven at 40°C for 45 seconds; rinse it with clean water, and dry it to obtain a composite nanofiltration membrane.

[0162] The composite nanofiltration membrane comprises: a base membrane; and an active layer formed on the upper surface of the base membrane; the thickness of the active layer is 30 nm.

[0163] Example 5

[0164] 1) preparing p-CCG-COF-TpPa-1 according to step S4); wherein the COF powder is TpPa-1 powder;

[0165] 2) Preparation of aqueous solution:

[0166] Mixing m-phenylenediamine, sodium dodecyl sulfate, sodium hydroxide, p-CCG-COF-TpPa-1 and water to obtain an aqueous phase solution; in the aqueous phase solution, the mass content of m-phenylenediamine is 1.2%, the mass content of sodium dodecyl sulfate is 0.05%, the mass content of sodium hydroxide is 0.5%, and the mass content of p-CCG-COF-TpPa-1 is 0.5%;

[0167] 3) Preparation of oil phase solution:

[0168] Dissolve terephthaloyl chloride in n-hexane to obtain an oil phase solution with a mass concentration of 0.2%;

[0169] 4) Immerse the polybenzimidazole membrane (base membrane, 150 μm) in the aqueous solution for 1 minute, take it out, roll the surface of the base membrane with a roller to squeeze it dry, and blow dry the excess liquid; then immerse it in the oil solution at 45°C for polymerization reaction for 20 seconds, take it out; dry it naturally in the air for 1 minute, and then heat treat it in an oven at 40°C for 45 seconds; rinse it with clean water, and dry it to obtain a composite nanofiltration membrane.

[0170] The composite nanofiltration membrane comprises: a base membrane; and an active layer formed on the upper surface of the base membrane; the thickness of the active layer is 30 nm.

[0171] Example 6

[0172] 1) preparing p-CCG-COF-TpBD according to step S4); wherein the COF powder is TpBD powder;

[0173] 2) Preparation of aqueous solution:

[0174] Mixing m-phenylenediamine, sodium dodecyl sulfate, sodium hydroxide, p-CCG-COF-TpBD and water to obtain an aqueous phase solution; in the aqueous phase solution, the mass content of m-phenylenediamine is 1.2%, the mass content of sodium dodecyl sulfate is 0.05%, the mass content of sodium hydroxide is 0.5%, and the mass content of p-CCG-COF-TpBD is 0.5%;

[0175] 3) Preparation of oil phase solution:

[0176] Dissolve trimesoyl chloride in n-hexane to obtain an oil phase solution with a mass concentration of 0.25%;

[0177] 4) Immerse the polybenzimidazole membrane (base membrane, 150 μm) in the aqueous solution for 1 minute, take it out, roll the surface of the base membrane with a roller to squeeze it dry, and blow dry the excess liquid; then immerse it in the oil solution at 45°C for polymerization reaction for 20 seconds, take it out; dry it naturally in the air for 1 minute, and then heat treat it in an oven at 40°C for 45 seconds; rinse it with clean water, and dry it to obtain a composite nanofiltration membrane.

[0178] The composite nanofiltration membrane comprises: a base membrane; and an active layer formed on the upper surface of the base membrane; the thickness of the active layer is 30 nm.

[0179] Example 7

[0180] 1) preparing p-CCG-COF-TpBD according to step S4); wherein the COF powder is TpBD powder;

[0181] 2) Preparation of aqueous solution:

[0182] Mixing m-phenylenediamine, sodium dodecyl sulfate, sodium hydroxide, p-CCG-COF-TpBD and water to obtain an aqueous phase solution; in the aqueous phase solution, the mass content of m-phenylenediamine is 1.2%, the mass content of sodium dodecyl sulfate is 0.05%, the mass content of sodium hydroxide is 0.5%, and the mass content of p-CCG-COF-TpBD is 0.5%;

[0183] 3) Preparation of oil phase solution:

[0184] Dissolve trimesoyl chloride in n-hexane to obtain an oil phase solution with a mass concentration of 0.25%;

[0185] 4) Immerse the polyethersulfone membrane (base membrane, 150 μm) in the aqueous solution for 1 minute, take it out, roll the surface of the base membrane with a roller to squeeze it dry, and blow dry the excess liquid; then immerse it in the oil solution at 45°C for polymerization reaction for 20 seconds, take it out; dry it naturally in the air for 1 minute, and then heat treat it in an oven at 40°C for 45 seconds; rinse it with clean water, and dry it to obtain a composite nanofiltration membrane.

[0186] The composite nanofiltration membrane comprises: a base membrane; and an active layer formed on the upper surface of the base membrane; the thickness of the active layer is 30 nm.

[0187] Comparative Example 1

[0188] 1) Preparation of aqueous solution:

[0189] Mix piperazine, sodium dodecyl sulfate, sodium hydroxide and water to obtain an aqueous phase solution; in the aqueous phase solution, the mass content of piperazine is 1.2%, the mass content of sodium dodecyl sulfate is 0.05%, and the mass content of sodium hydroxide is 0.5%;

[0190] 2) Preparation of oil phase solution:

[0191] Dissolve trimesoyl chloride in n-hexane to obtain an oil phase solution with a mass concentration of 0.2%;

[0192] 3) Immerse the polyethersulfone membrane (base membrane, 150 μm) in the aqueous solution for 1 min, take it out, roll the surface of the base membrane with a roller to squeeze it dry, and blow dry the excess liquid; then immerse it in the oil solution at 45°C for polymerization reaction for 20 seconds, take it out; dry it naturally in the air for 1 min, and then heat treat it in an oven at 40°C for 45 seconds; rinse it with clean water, and dry it to obtain a composite nanofiltration membrane.

[0193] The composite nanofiltration membrane comprises: a base membrane; and an active layer formed on the upper surface of the base membrane; the thickness of the active layer is 80 nm.

[0194] Comparative Example 2

[0195] 1) Preparation of aqueous solution:

[0196] Mix piperazine, sodium dodecyl sulfate, sodium hydroxide, p-CCG and water to obtain an aqueous phase solution; in the aqueous phase solution, the mass content of piperazine is 1.2%, the mass content of sodium dodecyl sulfate is 0.05%, the mass content of sodium hydroxide is 0.5%, and the mass content of p-CCG is 0.1%;

[0197] 2) Preparation of oil phase solution:

[0198] Dissolve trimesoyl chloride in n-hexane to obtain an oil phase solution with a mass concentration of 0.2%;

[0199] 3) Immerse the polyethersulfone membrane (base membrane, 150 μm) in the aqueous solution for 1 min, take it out, roll the surface of the base membrane with a roller to squeeze it dry, and blow dry the excess liquid; then immerse it in the oil solution at 45°C for polymerization reaction for 20 seconds, take it out; dry it naturally in the air for 1 min, and then heat treat it in an oven at 40°C for 45 seconds; rinse it with clean water, and dry it to obtain a composite nanofiltration membrane.

[0200] The composite nanofiltration membrane comprises: a base membrane; and an active layer formed on the upper surface of the base membrane; the thickness of the active layer is 80 nm.

[0201] Comparative Example 3

[0202] 1) Preparation of aqueous solution:

[0203] Mixing m-phenylenediamine, sodium dodecyl sulfate, sodium hydroxide, COF-TpPa-NH2 and water to obtain an aqueous phase solution; in the aqueous phase solution, the mass content of m-phenylenediamine is 1.2%, the mass content of sodium dodecyl sulfate is 0.05%, the mass content of sodium hydroxide is 0.5%, and the mass content of COF-TpPa-NH2 is 0.1%;

[0204] 2) Preparation of oil phase solution:

[0205] Dissolve trimesoyl chloride in n-hexane to obtain an oil phase solution with a mass concentration of 0.2%;

[0206] 3) Immerse the polyethersulfone membrane (base membrane, 150 μm) in the aqueous solution for 1 min, take it out, roll the surface of the base membrane with a roller to squeeze it dry, and blow dry the excess liquid; then immerse it in the oil solution at 45°C for polymerization reaction for 20 seconds, take it out; dry it naturally in the air for 1 min, and then heat treat it in an oven at 40°C for 45 seconds; rinse it with clean water, and dry it to obtain a composite nanofiltration membrane.

[0207] The composite nanofiltration membrane comprises: a base membrane; and an active layer formed on the upper surface of the base membrane; the thickness of the active layer is 50 nm.

[0208] The membrane separation performance of the composite nanofiltration membranes of Examples 1 to 7 and Comparative Examples 1 to 3 was tested:

[0209] The effective area is 15.3cm 2 The test membrane pool was stirred at a constant speed of 650 rpm to reduce concentration polarization. At a pressure of 0.50 MPa, MgCl2·6H2O, NaCl, and Na2SO4 were used as influent solutions to test the salt concentration of the feed solution and the permeate water. Before the test, the membrane was pre-pressed at a pressure of 10 bar for at least 30 minutes until the permeate reached a stable value.

[0210] Organic solvent permeation flux (P, Lm −2 h −1 bar −1 ) is determined according to formula (1):

[0211] Formula (1);

[0212] In formula (1), ΔV: volume of the collected permeate sample, L;

[0213] A: effective area of ​​the test membrane, m 2 ;

[0214] Δt: test time, h;

[0215] ΔP: applied transmembrane pressure, bar.

[0216] The solute removal rate (%) is calculated according to formula (2):

[0217] Formula (2);

[0218] In formula (2), Cp is the concentration of solute in the permeate (measured by UV-visible spectrophotometer), mg / L; Cf is the concentration of solute in the feed solution (measured by UV-visible spectrophotometer), mg / L.

[0219] The test results are shown in Table 1.

[0220] Table 1 Membrane separation performance of the composite nanofiltration membranes of Examples 1 to 7 and Comparative Examples 1 to 3

[0221]

[0222] As can be seen from Table 1, the membrane prepared in the embodiment of the present invention has a higher flux and a lower NaCl retention rate than the blank PA membrane, indicating that the membrane prepared in the present invention has better hydrophilicity and a larger pore size. Compared with the comparative example, the membrane prepared in the embodiment of the present invention has a higher MgCl2·6H2O retention rate at a thinner thickness, and the removal rate of Na2SO4 and MgSO4 remains relatively good. It can also be seen from the data that excessive p-CCG-COF-TpBD has a negative impact on the selective separation of the composite membrane. It may be that excessive ionic liquid (IL) will change the chemical bonds and hydrogen bonds of the PA layer, and then have an adverse effect on the membrane structure.

[0223] Test of heavy metal removal capacity of the composite nanofiltration membranes of Examples 1, 4 and Comparative Example 1:

[0224] The influent water with pH=5.0 contained 500 ppm Cu(NO3)2, Ni(NO3)2, Cr(NO3)3, and Zn(NO3)2, and the heavy metal ion retention and water flux were tested by the composite nanofiltration membranes of Examples 1, 4 and Comparative Example 1, respectively.

[0225] The test results are as follows Figures 1 to 4 And as shown in Table 2.

[0226] Figure 1 The composite nanofiltration membranes of Examples 1, 4 and Comparative Example 1 were used to measure Cu 2+ Removal rate of Figure 2 The composite nanofiltration membranes of Examples 1, 4 and Comparative Example 1 are Ni 2+ Removal rate of Figure 3 The composite nanofiltration membranes of Examples 1, 4 and Comparative Example 1 were used to measure the Cr 2+ Removal rate of Figure 4 The composite nanofiltration membranes of Examples 1, 4 and Comparative Example 1 were 2+ removal rate.

[0227] Table 2 Heavy metal removal capacity of the composite nanofiltration membranes of Examples 1, 4 and Comparative Example 1

[0228]

[0229] Depend on Figures 1 to 4 As shown in Table 2, the membrane of Comparative Example 1 had a high 2+ 、Ni 2+ Cr 3+ 、Zn 2+ The removal rates of the membrane in Example 1 were 54.8%, 91.4%, 52.3% and 56.4% respectively. 2+ 、Ni 2+ Cr 3+ 、Zn 2+The removal rates of the membrane in Example 4 were 91.4%, 92.4%, 89.4% and 84.2% respectively. 2+ 、Ni 2+ Cr 3+ 、Zn 2+ The removal rates were 90.2%, 92.0%, 92.3% and 94.5% respectively. The experimental results show that the positively charged IL-NH 3+ It can effectively increase the passage of heavy metal ions through the nanofiltration membrane.

[0230] The antibacterial properties of the composite nanofiltration membranes of Examples 1, 3, 5, 7 and Comparative Example 1 were tested:

[0231] The composite nanofiltration membrane (3.14 cm 2 ) were sterilized by ultraviolet irradiation (1 h) and then incubated with 20 μL of E. coli / S. aureus solution (1 × 10 6 CFU / m 2 ) was coated on the membrane surface. After culturing (37°C) for 4 hours, 1980 μL of liquid culture medium was used to collect E. coli. 50 μL of the mixed solution was inoculated in an agar plate and cultured in a 37°C incubator for 24 hours. Finally, the number of bacterial colonies was counted. The results are shown in Figures 5 and 6 shown. Figure 5 The antibacterial effect of the composite nanofiltration membranes of Examples 1, 3, 5, 7 and Comparative Example 1 on Escherichia coli; Figure 6 The antibacterial effect of the composite nanofiltration membranes of Examples 1, 3, 5, 7 and Comparative Example 1 on Staphylococcus aureus. Figures 5 and 6 It can be seen that regarding the number of colonies in the culture medium, the examples did not exceed that of the comparative example 1, indicating that the antibacterial effect of the composite nanofiltration membranes of the examples was higher than that of the composite nanofiltration membranes of the comparative example 1.

[0232] Figure 7 The infrared spectra of PA, COF-TpPa, p-CCG and p-CCG-COF-TpPa-PA.

[0233] FTIR spectrum a shows that at about 1164 cm −1 At 1238 cm, the imidazole ring produced CH3(N) stretching peak, CH2(N) stretching peak and asymmetric stretching peak within the ring plane, indicating the presence of IL-NH2 containing an amine terminal. -1 (CN) and 1595cm -1 The presence of (C=C) indicates that COF is also involved in the formation of the composite film. -1 The disappearance of C=O in the carboxyl group indicates that the negatively charged carboxylic acid group and the positively charged IL-NH3 +The group reaction, combined with the Zeta potential, showed that the p-CCG-COF-TpPa-PA composite membrane was successfully formed.

[0234] Figure 8 The surface charge properties of the composite nanofiltration membranes of Examples 2, 4, 6 and Comparative Example 1. The surface charge properties of the membranes were measured by a Zeta potential analyzer. It was found that the isoelectric points of Examples 2, 4 and 6 were 7.2, 7.4 and 8.3, respectively. It can be seen that the composite membranes exhibit positive charge properties in a wider pH range. This is due to the p-CCG cation RN + and -NH + -Results. According to the Donnan effect, p-CCG and I-COFs regulate the strong positive charge of the membrane, which will give the membrane a higher H / RE 3+ Selectivity. Compared with the membrane without adding p-CCG and I-COFs, it has a lower surface potential and is more conducive to the removal of metal ions.

[0235] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A nanofiltration membrane comprising: Basement membrane; and an active layer formed on the upper surface of the base film; The active layer is formed by interfacial polymerization of an aqueous solution and an oily solution and then heat treatment; The solute of the aqueous phase solution consists of an aqueous phase monomer, a surfactant, sodium hydroxide and p-CCG-COF-TpPa / TpBD; in the aqueous phase solution, the mass content of p-CCG-COF-TpPa / TpBD is 0.05% to 5%; The p-CCG-COF-TpPa / TpBD is prepared by ultrasonication and filtration of p-CCG dispersion and COF solution; The p-CCG is obtained by modifying graphene oxide nanosheets with 1-(3-aminopropyl)-3-methylimidazole brominating agent; The base film is made of at least one of polyphenylsulfone, polyaniline, polysulfone, polyetheretherketone, polyimide, polybenzimidazole, polyvinylidene fluoride and polyethersulfone.

2. The nanofiltration membrane according to claim 1, characterized in that The COF is at least one of TpPa-1, TpPa-2, TpPa-NH2, TpPa-F4, TpBD, TpBD-Me2 and TpBD-(OMe)2.

3. The nanofiltration membrane according to claim 1, characterized in that The preparation method of p-CCG comprises the following steps: After mixing the aqueous dispersion of graphene oxide nanosheets and 1-(3-aminopropyl)-3-methylimidazole brominating agent, the pH value of the mixed solution is adjusted to 7.5-8.5, and after ultrasonic treatment, heated and stirred, and centrifuged, p-CCG is obtained.

4. The nanofiltration membrane according to claim 1, characterized in that The preparation method of the p-CCG-COF-TpPa / TpBD comprises the following steps: After mixing the p-CCG dispersion with the COF solution, ultrasonic treatment and vacuum filtration were performed to obtain p-CCG-COF-TpPa / TpBD; In the aqueous solution, the mass content of p-CCG-COF-TpPa / TpBD is 0.05%~5%.

5. The nanofiltration membrane according to claim 1, characterized in that The aqueous phase monomer includes at least one of m-phenylenediamine, p-phenylenediamine, piperazine, polyethyleneimine, 3,5-diamino-N-(4-aminophenyl)benzamide and imine COFs; In the aqueous phase solution, the mass content of the aqueous phase monomer is 1% to 3%.

6. The nanofiltration membrane according to claim 1, characterized in that The surfactant comprises at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and sodium fatty alcohol ether sulfate; In the aqueous phase solution, the mass content of the surfactant is 0.01% to 1%.

7. The nanofiltration membrane according to claim 1, characterized in that In the aqueous phase solution, the mass content of sodium hydroxide is 0.2% to 3.5%.

8. The nanofiltration membrane according to claim 1, characterized in that The oil phase solution consists of acyl chloride and an organic solvent; The acyl chloride comprises at least one of phthaloyl chloride, isophthaloyl chloride, terephthaloyl chloride, trimesoyl chloride and pyromellitoyl chloride; In the oil phase solution, the mass concentration of acyl chloride is 0.1% to 0.3%; The organic solvent includes at least one of trichlorotrifluoroethane, n-hexane, cyclohexane, isopar G, isopar M, isopar L and heptane.

9. A method for preparing the nanofiltration membrane according to any one of claims 1 to 8, comprising the following steps: The base membrane is immersed in an aqueous solution, taken out and dried, immersed in an oil solution for polymerization, taken out, and subjected to heat treatment to obtain a nanofiltration membrane; The solute of the aqueous phase solution consists of an aqueous phase monomer, a surfactant, sodium hydroxide and p-CCG-COF-TpPa / TpBD; The p-CCG-COF-TpPa / TpBD is prepared by ultrasonication and filtration of p-CCG dispersion and COF solution; The p-CCG is obtained by modifying graphene oxide nanosheets with 1-(3-aminopropyl)-3-methylimidazole brominating agent.

Citation Information

Patent Citations

  • Nanofiltration membrane and preparation method thereof

    CN117358066A

Cited By

  • Positively-charged composite membrane based on sulfonated COF interlayer and application of positively-charged composite membrane

    CN120662149A